A thermal study on workpiece during turning process - Faris Aidil Mohamed Daud (School of Manufacturing Engineering, University Malaysia Perlis, 2016)
During a turning process, heat is generated at the edge of the cutting tool. This heat is then dissipated through the four systems that make up the process which are the cutting tool, the workpiece the chip fored and the cutting fluid. This heat, either generated or dissipated, can be said to detemine the efficiency of the machining process such as the material remove rate.